PREPARATION OF IN - HOUSE COCOA FLOUR RMs AND DETERMINATION OF ITS Cd CONTENT BY USING GFAAS - Anna E. Persulessy (Research Center for Chemistry - LIPI, 2009)
In-house cocoa flour RMs instead of CRMs was prepared and checked of its homogeneity and stability. Due to CRMs are limited availability in terms of matrices of concern and costly (high production cost) making in-house cocaflour RMs is alternatively used for daily quality control in the laboratory. The analysis method for reliable checking of homogeneity and stability of cadmium content in the in-house cocoaflour RMs was studied. The effects of magnesium nitrate and lanthanum/magnesium nitrate as chemical modifiers in the determination of cadmium in cocoaflour by GFAAS were studied as well. Detection limit of method was estimated to be 0.07 ug L'(calcuiaied as 3Sy;/slope of calibration curve) and calibration curve of working range was linear. The results analysis for candidate of in-house cocoaflour RMs reveals the consistence results and no variability between and within-bottle observedat 95% limit of confidence and stabile during the period of time observed.